A new method to quantify how water repellency compromises soils' filtering function. (10th March 2014) - Müller, K.; Deurer, M.; Kawamoto, K.; Kuroda, T.; Subedi, S.; Hiradate, S.; Komatsu, T.; Clothier, B. E.
Summary Soil water repellency (SWR) is known to lead to preferential flow and to degrade the soil's filtering efficiency. However, no method is available to quantify directly how SWR affects the transport of reactive solutes. We propose a new method for conducting solute transport experiments in water‐repellent soils. It involves sequentially applying two liquids, one water, the other a reference fully wetting liquid, namely aqueous ethanol, to the same intact soil core with air‐drying between liquids. We applied this approach to quantify the impact of SWR on the filtering of the herbicide 2, 4‐Dichlorophenoxyacetic acid (2, 4‐D) in two Andosols. In batch experiments conducted prior to the transport experiments, 2, 4‐D sorption was not influenced by aqueous ethanol for one soil. However, sorption in the second soil followed the co‐solvency theory, which predicts decreasing sorption with increasing solvent fractions. Thus, sorption experiments are necessary to complement our new method. Breakthrough curves were characterized by preferential flow with large initial concentrations, tailing and a long prevalence of solutes remaining in the soil. In the soil in which 2, 4‐D sorption was unaffected by aqueous ethanol, SWR increased 2, 4‐D losses by four and 50 times in the first 5‐mm outflow compared with the 2, 4‐D losses with water. After 50‐mm outflow, the 2, 4‐D losses were similar for one core, but in the other core they were still about four times greater with water than with aqueous ethanol. This method to quantify the reduction of the soil's filtering efficiency by SWR is needed for assessing the increased risk of groundwater contamination by solutes exogenously applied to water‐repellent soils.